Configuration of the parameters for scanner-based track detector evaluation system - Csordás Anita (Nukleonika, 2020)
According to the new European Union Basic Safety Standards (EU-BSS), preparation of the National Radon Action Plan is obligatory for the Member States. One of the plan’s aims is to carry out an indoor radon survey to identify radon-prone areas. In the radon surveys, track detector methods are used. At the University of Pannonia (Veszprém, Hungary), a new scanner-based detector evaluation system has been developed. For the application of the new system, the selection of appropriate parameters is necessary. In this study, selection of the applied track detectors and setting of the etching conditions have been carried out. Two different types of allyl diglycol carbonate (ADC or CR-39) track detectors were investigated, taking into account the detector’s background and response during the exposure (determination of calibration factor). The Baryotrak’s background track density (0–1.5 tracks mm−2) was lower than that of the 0.8–4 tracks mm−2. The response of the Tastrak was higher, but the deviation of the calibration factor was much higher (1.2–5.3 × 10−3 tracks mm−2/(Bq day m−3)) than in the case of the Baryotrak (1.4–2.8 × 10−3 tracks mm−2/(Bq day m−3)). After the systematic review of the etching system, a new method was developed. For the determination of the optimal track diameter, the argon fluoride (ArF) laser was applied to create tracks with diameters in the range of 10–100 μm. The optimum track size was in the range of 40–60 μm. On this basis, new etching conditions were determined: 6.25 M NaOH solution, a temperature of 90°C, and time period of 8 hours.